Fixed point and coincidence point theorems for a pair of single-valued and multi-valued maps on a metric space - S. Venkata Ratnam Naidu (International Journal of Mathematics and Mathematical Sciences)
We obtain fixed point and coincidence point theorems for a pair of single-valued and multi-valued maps on a metric space satisfying a generalized nonexpansive type condition.